Hybrid ECMO for a patient in respiratory failure developing cardiac insufficiency. (April 2016) - Youdle, Jemma; Penn, Sarah; Maunz, Olaf; Simon, Andre
A 45-year-old patient in lung failure treated with veno-venous extracorporeal membrane oxygenation (VV ECMO) developed subsequent right heart failure and required cardiac support. We present a method of upgrading a VV ECMO to a hybrid system for simultaneous support for respiratory and cardiac failure.